Use Of 4k Model In Forming 21st Century Skills In Primary Class Students (Eurasian Journal of Learning and Academic Teaching, 2024)
In the article, improving the quality of education, modern education, how a modern teacher should teach a student today, 4K model, 4K skills, updated textbooks of primary classes, effective use of modern methods in lessons issues have been considered.